Demand estimation of mass‐gathering healthcare in developing countries: The case of Kumbh Mela in India. (16th February 2021) - Zhao, Tiancheng; Ye, Han; Mukherjee, Ujjal Kumar; Chhajed, Dilip
Abstract: A mass‐gathering is defined as a congregation of a relatively large number of people in a specific location for a specific purpose over a short duration of time. Managing Mass‐Gathering Healthcare (MGH), especially in resource‐constrained regions, is a key policy challenge. Planning and preparation for MGH require understanding the sources, and estimation of demand. We propose a spatio‐temporal Poisson point process model for MGH demand estimation that considers the associated risk factors. We analyze admissions data from a multi‐specialty hospital in Ujjain, India, spanning a period before, during, and after Kumbh Mela, one of the larger religious gatherings globally. The results show that the effect of mass‐gathering on hospital admissions is heterogeneous across disease groups. We identify key socio‐economic and healthcare infrastructural factors that are associated with MGH demand. We establish the external‐validity of the results by demonstrating that mass‐gatherings generally increase the spatial dependence across regions, particularly where availability of healthcare infrastructure is relatively low. Finally, we discuss policy insights for managing MGH.